Cultural landscape: a new paradigm for landscape architecture - Md Jani, Haza Hanurhaza; Mohd. Hussain, Mohd. Ramzi (2011)
This paper presents the review on the important of cultural landscape in the context of landscape architecture’s profession. It is crucial to understand the concept of cultural landscape as it offers main contribution in sustaining the heritage value and protecting local identity and original culture of a group of people or place. From Islamic point of view, cultural landscape present the notion of revealing and sustaining the great diversity of the interactions between humans and their environment, to protect living traditional cultures and preserve the traces of those which have disappeared. Therefore cultural landscape must be incalculate with profession of landscape architect and this concept should be perceived as an added value in landscape architecture education in Asia. This paper is based on three fundamental framework of appreciating cultural landscape which is history, heritage and culture which cover the explanation of human root, identity, image, character and values. It is hoped that the output of the paper will contribute to further enrich landscape architecture’s profession on ideas, innovations and added values for landscape architect in future generation.